'We are all in the same boat': How societal discontent affects intention to help during the COVID‐19 pandemic. (8th October 2021) - Resta, Elena; Mula, Silvana; Baldner, Conrad; Di Santo, Daniela; Agostini, Maximilian; Bélanger, Jocelyn J.; Gützkow, Ben; Kreienkamp, Jannis; Abakoumkin, Georgios; Khaiyom, Jamilah Hanum Abdul; Ahmedi, Vjollca; Akkas, Handan; et al.
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has caused a global health crisis. Consequently, many countries have adopted restrictive measures that caused a substantial change in society. Within this framework, it is reasonable to suppose that a sentiment of societal discontent, defined as generalized concern about the precarious state of society, has arisen. Literature shows that collectively experienced situations can motivate people to help each other. Since societal discontent is conceptualized as a collective phenomenon, we argue that it could influence intention to help others, particularly those who suffer from coronavirus. Thus, in the present study, we aimed (a) to explore the relationship between societal discontent and intention to help at the individual level and (b) to investigate a possible moderating effect of societal discontent at the country level on this relationship. To fulfil our purposes, we used data collected in 42 countries ( N = 61, 734) from the PsyCorona Survey, a cross‐national longitudinal study. Results of multilevel analysis showed that, when societal discontent is experienced by the entire community, individuals dissatisfied with society are more prone to help others. Testing the model with longitudinal data ( N = 3, 817) confirmed our results. Implications for those findings are discussed in relation to crisis management. Please refer to the Supplementary Material section to find this article's Community and Social Impact Statement .